The Gothic and Grotesque in Barbara Gowdy’s Mister Sandman - Staels, Hilde (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2012)
The fiction of Barbara Gowdy is peopled with physically or spiritually aberrant characters that can trigger shock and disgust in readers. Her novel Mister Sandman (1995), however, calls for a more nuanced response to "the unusual," one triggered by Gowdy's parodic use of the gothic and grotesque as well as by instances of humour, comic relief, and a light-hearted tone. Such a combination of literary modes arouses sympathy for the novel's "monstrous" characters, making Mister Sandman representative of what Catherine Spooner calls the "Gothic-Carnivalesque." The novel's parodic rewriting of E.T.A. Hoffmann's short story "Der Sandmann" (1816), and Gowdy's use of grotesque imagery to produce humour rather than horror, are emblamatic of what Avril Horner and Sue Zlosnik call "the comic turn" in contemporary gothic fiction, and complicate the traditional concepts of the grotesque articulated by Wolfgang Kayser and Mikhail Bakhtin